KEBIJAKAN PENDIDIKAN INKLUSIF, IMPLEMENTASI YANG ABAI KONTEKS LINGKUNGAN SOSIAL - Ika Arinia Indriyany (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2017)
This study is going to discuss the implementation of inclusive education’s policy in Yogyakarta. Yogyakarta is a famous for being one of the friendliest city for people with disabilities (some people often refer to handicapped person, although that term is considered to new discrimination by the activist). Inclusive education’s policy is a breakthrough in education policy that puts people with disability and non-disability to sit and learn together in one classroom. In the national area, inclusive education policies stated in Permendiknas No 70 of 2009, while in Yogyakarta contained in Pergub DIY No 21 of 2013. Implementation of that policies did not reach 100% yet. Because, the policy makers forgot the social context, whether society ready to including people with disability in their life or not. Keywords: inclusive education policy, implementation, social context, social inclusion